Reliability and validity of the finnish version of the neck disability index and the modified neck pain and disability scale - Salo, Petri; Ylinen, Jari; Kautiainen, Hannu; Arkela-Kautiainen, Marja; Häkkinen, Arja (Spine (Philadelphia, Pa. 1976), 2010)
Translation and psychometric testing. To cross-culturally adapt the Neck Disability Index (NDI) to the Finnish language and to assess the reliability and validity of the Finnish version of the Neck Disability Index (NDI-FI) and the modified Neck Pain and Disability Scale (mNPDS-FI) in Finnish patients with neck pain. Although largely used, no previous reports exist on the translation process or the testing of the psychometric properties of the Finnish version of the NDI or the mNPDS used in Finland. The translation of the questionnaire from English into Finnish was done in accordance with the published guidelines. A total of 101 patients with neck pain participated in the study. The reliability of the questionnaires was tested using a test-retest procedure at 2-week intervals. Further psychometric testing was done by assessing the construct validity and internal consistency of the questionnaires. Test-retest reliability (intraclass correlation coefficients) was excellent for the NDI-FI (0.94) and mNPDS-FI (0.91). Factor analysis identified 1 factor for the NDI-FI and 3 factors for the mNPDS-FI; pain intensity, work ability, and activities of daily living. The internal consistency value (Cronbach alpha) for the NDI-FI was 0.85, and 0.84, 0.83, and 0.82, respectively, for the 3 factors of the mNPDS-FI. The correlation between neck pain and the NDI-FI was 0.58 (P < 0.001) and 0.72 for the mNPDS-FI (P < 0.001). A statistically significant linear relationship was observed between self-estimated coping and the outcomes of the NDI-FI and the mNPDS-FI. The NDI-FI and the mNPDS-FI are reliable, valid instruments for assessing disability among Finnish patients with neck pain.